ИМПРЕССИОНИСТИЧЕСКОЕ ХУДОЖЕСТВЕННОЕ СОЗНАНИЕ В РУССКОЙ И ЗАПАДНОЕВРОПЕЙСКОЙ ПРОЗЕ НАЧАЛА XX ВЕКА - Захарова, Виктория (Studia Rossica Posnaniensia, 2008)
At the beginning of the 20th century the renovation of the artistic mentality became very intensive in various spheres. Russian prose of the silver century was characterized by the processes of synthesis. The impressionistic artistic thinking was one of the dominants in this synthesis. In this article the impressionism was researched as a type of the artistic mentality. Characteristic properties of the impressionistic world outlook and poetics are demonstrated in the examples of the prose of such Russian writers as I. Bunin, B. Zaytsev, S. Sergeev-Tsensky and such Western-European writers as Goncourt brothers, M. Proust and K. Hamsun.